1999
DOI: 10.1073/pnas.96.14.8132
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and function of intrahepatic islet allografts in rhesus monkeys treated with humanized anti-CD154

Abstract: Reported effects of anti-CD154 treatment on autoimmunity, alloreactivity, and inf lammatory events mediated by macrophages and endothelial cells indicated that it might be an ideal agent for the prevention of intrahepatic islet allograft failure. This hypothesis was tested in MHCmismatched rhesus monkeys. Transplantation of an adequate number of viable islets resulted in engraftment and insulin independence in six of six recipients treated with anti-CD154 (hu5c8) induction plus monthly maintenance therapy (pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
250
3
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 397 publications
(259 citation statements)
references
References 50 publications
5
250
3
1
Order By: Relevance
“…Blockade of CD40-CD40L interactions by the use of anti-CD40L mAbs in mice (12)(13)(14)(15)(16)(17)(18) and primates (19,20) has resulted in prolongation of allograft survival. However, in only some of these studies, a fraction of the recipients showed long-term engraftment (12,17,19,20).…”
mentioning
confidence: 99%
“…Blockade of CD40-CD40L interactions by the use of anti-CD40L mAbs in mice (12)(13)(14)(15)(16)(17)(18) and primates (19,20) has resulted in prolongation of allograft survival. However, in only some of these studies, a fraction of the recipients showed long-term engraftment (12,17,19,20).…”
mentioning
confidence: 99%
“…40,41 A maintenance therapy with agents blocking T cell costimulation was required for the long-term survival of islets and kidneys allografted in non-human primate models. 5,9,10 The constant expression of CTLA4Ig may provide a means to prevent the late rejection events without the constraints of systemic treatments. However, the long-term efficacy of a sustained localized delivery remains to be tested with non-dividing cells.…”
Section: Figure 8 Photomicrographs Of Both Hind Limbs From a Dba/2j Mmentioning
confidence: 99%
“…7 CD154 blockade allowed the long-term survival of mouse islet allografts when combined with injections of donor small lymphocytes 8 and was recently reported to permit the acceptance of allogeneic islets in two non-human primate models. 9,10 Fewer studies, however, have evaluated the effect of these molecules on transplantation of other cell types. Intraperitoneal injections of CTLA4Ig combined with anti-CD4 monoclonal antibodies improved the efficiency of myoblast allotransplantation.…”
Section: Introductionmentioning
confidence: 99%
“…CD40 ligand (CD154) monoclonal antibodies (Anti-CD40L mAbs), alone or in combination with CTLA-4-immunoglobulin fusion protein (CTLA-4Ig), have been reported to induce long-term allograft survival and tolerance in a number of transplantation models (1)(2)(3)(4)(5)(6). The efficacy of these treatments can be variable and has been reported to be affected by the strain of the mouse recipient, the type of tissue transplanted, the age of the recipient and whether the response is a memory or naïve one (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%